Asia's Quest for Inclusive Growth Revisited - Aoyagi, Chie (IMF Working Papers; Working Paper, 2015)
Despite the rapid economic growth and poverty reduction, inequality in Asia worsened during last two decades. We focus on the determinants of growth inclusiveness and suggest options for reform. A cross cross-country empirical analysis suggests that fiscal redistribution, monetary policy aimed at macro stability, and structural reforms to stimulate trade, reduce unemployment and increase productivity are important determinants of inclusive growth. The main policy implication of our analysis is that there is still room to strengthen such policies in Asia to better achieve growth with shared prosperity. In particular, scenario simulations based on our results suggests that the effect of expanding fiscal redistribution on inclusive growth could be sizeable in emerging Asia, since the estimated improvement in our proxy of inclusive growth - a measure of growth in average income 'corrected' for the equity impact-ranges from about 1 to about 8 percentage points.